In vivo Confocal Microscopic Analysis of Limbal Stroma in Patients With Limbal Stem Cell Deficiency. Issue 11 (November 2015) - Unknown
Abstract : Purpose: Using in vivo confocal microscopy, we established that unique hyperreflective structures in the anterior limbal stroma of healthy individuals represent the limbal stromal niche. The aim of this study was to characterize the limbal stromal microarchitecture in patients with limbal stem cell deficiency (LSCD). Methods: After obtaining informed consent, 10 patients with LSCD and 3 with macular corneal dystrophy were recruited. In vivo confocal imaging of the limbus and cornea of the affected and normal eyes was performed using an HRT III laser scanning microscope, beyond the epithelium deep into the stroma. Results: In the case of LSCD, the limbal epithelium was replaced by conjunctival epithelium. A large number of inflammatory and dendritic cells were identified along with blood vessels from the epithelium to deep stromal layers. The unique hyperreflective niche structures were replaced by homogenously bright fibrous structures in all eyes with total LSCD. In patients with partial LSCD, even the clinically defined normal limbus had fibrotic stroma. In a patient with focal LSCD, only the affected limbal stroma remained fibrotic, whereas the adjacent clinically normal limbus had the unique hyperreflective structures. Although the opaque corneal stroma appeared bright because of proteoglycan deposition, it was possible to identify the normal limbal epithelial and stromal architecture in macular corneal dystrophy. Conclusions: In the case of LSCD, the limbal stromal niche was replaced by bright fibrotic structures indicating persistence of damage several months after injury. Further studies are required to characterize the sequential events occurring in the anterior limbal stroma after injury using this noninvasive method. Abstract : Supplemental Digital Content is Available in the Text.